Reading Victorian poetry - Cronin, Richard, 1949- (Hoboken, NJ : John Wiley & Sons, 2012)
Reading Victorian Poetry offers close readings of poems from the Victorian era by a renowned scholar. The selection includes a range of canonical and lesser known writers Skilfully conveys the breadth and diversity of nineteenth-century poetryOffers an ideal balance of canonical and less well-known writersAllows readers to explore the poetry of the Victorian era, through the eyes of one of the most renowned scholars in the fieldPoets covered include Matthew Arnold, Emily Brontë, Elizabeth Barrett Browning, Robert Browning, Lewis Carroll, A.H. Clough, G.M. Hopkins, Edward Lear, Christina Ro.
Introduction: The Victorian poetry palace -- The divided self and the dramatic monologue -- Victorian metrics -- Short poems, long poems, and the Victorian sonnet sequence -- Victorian poetry and translation -- Victorian poetry and life -- Poetry and religion -- Conclusion: The 1890s.
Includes bibliographical references and index.
Keywords: 1800-1899; English poetry -- 19th century -- History and criticism; Literature and society -- Great Britain -- History -- 19th century; Poetics -- History -- 19th century; Literature and society -- Great Britain -- History -- 19th century; Poetics -- History -- 19th century; Literature; POETRY -- English, Irish, Scottish, Welsh; English poetry; Literature and society; Poetics; Great Britain; Electronic books; Criticism, interpretation, etc; History